COMPARATIVE STUDY OF LEAF AND STEM BARK EXTRACTS OF PARKIA BIGLOBOSA AGAINST ENTEROBACTERIA. - Millogo-Kone, H.; Guissou, I. P.; Nacoulma, O.; Traore, A. S. (African Journal of Traditional, Complementary and Alternative Medicines, 2008)
Hydroethanolic and aqueous extracts of leaf and stem bark of Parkia biglobosa (Jacq) Benth. (Mimosaceae) were tested against clinical isolates Escherichia coli, Salmonella typhi, Shigella dysenteriae and Enterococcus faecalis, and corresponding collection strains E. coli CIP 105 182, Salmonella enterica CIP 105 150, Shigella dysenteriae CIP 54-51 and Enterococcus faecalis CIP 103 907. Discs of Gentamicin, a broad spectrum antibiotic were used as positive controls. The results showed all the extracts possess antimicrobial activities. A comparative study of the antibacterial activity of the leaves and that of the barks showed that for all the tested microorganisms, the hydroalcoholic extract of the bark is more active than the aqueous extract of the leaf. he hydroethanolic extract of the leaves is as effective as the aqueous extract of the stem bark prescribed by the traditional healer. The phytochemical screening showed that sterols and triterpenes, saponosides, tannins, reducing compounds, coumarins, anthocyanosides, flavonosides are in both bark and leaf but in different concentrations.